Induction and effector functions of TH17 cells - Bettelli, Estelle; Korn, Thomas; Oukka, Mohamed; Kuchroo, Vijay K. (Nature (London), 2008)
T helper 17 cells: Induction and effector functions The recently discovered T H 17 cells, the third subset of effector T helper cells, are the subject of intensive research. They produce the cytokine interleukin-17, coordinate defence against specific pathogens and mediate tissue inflammation. Bettelli et al . review this fast-moving field, focusing on the emergence of the balance between pro-inflammatory TH17 cells and inhibitory T reg cells as key factor in many inflammatory and autoimmune diseases. T helper (T H ) cells constitute an important arm of the adaptive immune system because they coordinate defence against specific pathogens, and their unique cytokines and effector functions mediate different types of tissue inflammation. The recently discovered T H 17 cells, the third subset of effector T helper cells, have been the subject of intense research aimed at understanding their role in immunity and disease. Here we review emerging data suggesting that T H 17 cells have an important role in host defence against specific pathogens and are potent inducers of autoimmunity and tissue inflammation. In addition, the differentiation factors responsible for their generation have revealed an interesting reciprocal relationship with regulatory T (T reg ) cells, which prevent tissue inflammation and mediate self-tolerance.